2010
DOI: 10.1371/journal.pcbi.1000840
|View full text |Cite
|
Sign up to set email alerts
|

Action Potential Energy Efficiency Varies Among Neuron Types in Vertebrates and Invertebrates

Abstract: The initiation and propagation of action potentials (APs) places high demands on the energetic resources of neural tissue. Each AP forces ATP-driven ion pumps to work harder to restore the ionic concentration gradients, thus consuming more energy. Here, we ask whether the ionic currents underlying the AP can be predicted theoretically from the principle of minimum energy consumption. A long-held supposition that APs are energetically wasteful, based on theoretical analysis of the squid giant axon AP, has recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
312
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(338 citation statements)
references
References 38 publications
25
312
1
Order By: Relevance
“…This work updates our previous estimation of energy use associated with neural computation in the cerebral cortex (Attwell and Laughlin, 2001) and cerebellum (Howarth et al, 2010), incorporating recently published data demonstrating that action potentials are more energy efficient than previously assumed (Alle et al, 2009;Carter and Bean, 2009;Sengupta et al, 2010). Updating the models in this way supports most of the major conclusions of the original papers.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This work updates our previous estimation of energy use associated with neural computation in the cerebral cortex (Attwell and Laughlin, 2001) and cerebellum (Howarth et al, 2010), incorporating recently published data demonstrating that action potentials are more energy efficient than previously assumed (Alle et al, 2009;Carter and Bean, 2009;Sengupta et al, 2010). Updating the models in this way supports most of the major conclusions of the original papers.…”
Section: Discussionsupporting
confidence: 71%
“…For the much smaller granule cells, which each receive a far smaller number of excitatory synaptic inputs (B4: Eccles et al, 1967), but have to maintain the resting potential of a very long (B4.5 mm) axon, most of the signaling energy ( Figure 3B) goes on the resting potential (71%, a significantly larger percentage than the previously calculated value of 55%: Howarth et al, 2010). Recent modeling studies have suggested that the temporal overlap between Na + and K + currents during a cerebellar granule cell action potential is negligible, resulting in an overlap factor of only 1.04, implying an extremely energy efficient action potential (Sengupta et al, 2010). As a result, granule cells are predicted to use only a small fraction of their energy on action potentials (10%; Figure 3B), much less than the previous prediction that 31% of granule cell signaling energy use is on action potentials (Howarth et al, 2010).…”
Section: Energy Consumption By Subcellular Processes In the Cerebellummentioning
confidence: 71%
See 2 more Smart Citations
“…The number of neurons in the MB and AL appear to be similar in our study species; O. smaragdina majors, however, have larger MB neurons (J. F. Kamhi, J. F. A. Traniello 2016, unpublished data). This appears counterintuitive, although neurons may be optimized to reduce ATP consumption [74] and thus COX activity, which is linked to neural activation [35] and not necessarily directly correlated with neuron size. Behavioural phenotype also may be related to brain metabolic activity [75].…”
Section: (B) Colony-level Social Organization and Brain Evolutionmentioning
confidence: 99%